Advances in Emotion Regulation: From Neuroscience to Psychotherapy - Remo Job; Alessandro Grecucci; Jon J. Frederickson (Frontiers Media SA, 2017)
Emotions are the gift nature gave us to help us connect with others. Emotions do not come from out of nowhere. Rather, they are constantly generated, usually by stimuli in our interpersonal world. They bond us to others, guide us in navigating our social interactions, and help us care for each other. Paraphrasing Shakespeare, (3z(BOur relationships are such stuff as emotions are made of(3y(B. Emotions express our needs and desires. When problems happen in our relationships, emotions arise to help us fixing those problems. However, when emotions can become dysregulated, pathology begins. Almost all forms of psychopathology are associated with dysregulated emotions or dysregulatory mechanisms. These dysregulated emotions can become regulated when the therapist helps clients express, face and regulate their emotions, and channel them into healthy actions. This research topic gathers contributions from affective neuroscientists and psychotherapists to illustrate how our emotions become dysregulated in life and can become regulated through psychotherapy.s
English
Keywords: cognitive behavioral therapy; affective Neuroscience; emotion regulation; psychopathology; affective disorders; psychotherapy; psychodynamic psychotherapy